Integrated stratigraphy of Pliensbachian and Toarcian strata from the northern Neuquén Basin, Argentina - Storm, Marisa S. (2024)
The Toarcian Oceanic Anoxic Event (T-OAE, ~183 Ma) was marked by globally recognized environmental perturbations, most notably disturbances to the global carbon cycle and climate. To date, geochemical records providing information about the T-OAE have been largely generated from the warm temperate climate zone of the NW European realm. Coeval geochemical records from the Southern Hemisphere, providing a more global perspective on palaeoenvironmental changes associated with the T-OAE, are comparatively scarce. In this study, we present a biostratigraphically calibrated litho- and chemostratigraphic recordof Lower Jurassic strata from the northern Neuquén Basin, Argentina, covering the Upper Pliensbachian and Toarcian upper tenuicostatum to lower Dumortieria Andean ammonite zones, equivalent to the uppermost tenuicostatum to pseudoradiosa European standard zones. The integrated stratigraphic data re-define the stratigraphic position of the Andean tenuicostatum–D. hoelderi ammonite Zone boundary and support near-synchroneity of this horizon with the tenuicostatum–serpentinum zonal boundary in NW Europe. The stratigraphic interval recording the negative carbon-isotope excursion associated with the T-OAE appears massively expanded and organic lean in contrast to the coeval organic-rich deposits in other parts of the Neuquén Basin and in European sections. At Las Overas, persistent sedimentary organic-matter enrichment was limited to brief intervals of black-shale deposition, possibly coinciding with reduced sedimentary organic matter dilution. Depositional rates and inorganic redox proxies suggest that the development of oxygen-depleted conditions may have been disrupted by the interplay between basin subsidence, sedimentation rate, relative sea-level change, depositional setting and deep-water currents.